Deciphering the immunological landscape of HR + metastatic breast cancer: insights from single-cell transcriptomics - Lifang He; Qianqian Zhao; Zexiao Chen; Lijuan He; Zhaochang Qi; Jundong Wu; Kexiang Zhou; Yukun Cui (Human Cell, 2026)
Breast cancer remains the leading cause of cancer-related mortality among women worldwide, primarily due to metastatic complications. The immune components of the tumor microenvironment (TME) significantly influence metastatic progression. The objective of this study was to uniquely characterize the TME of hormone receptor-positive (HR +) breast cancer with a focus on ovarian metastasis using single-cell RNA sequencing. We delineated the cellular architecture of breast cancer tissues. A total of 9 cell types in 18 clusters were identified, including T cell, B cell and plasma, macrophage, neutrophil, fibroblast, macrophage, endothelial, basal, luminal, SMC (smooth muscle cells) and proliferation cells. Furthermore, macrophages were divided into tumor-associated macrophages and monocyte macrophages, with detailed marker gene analysis. Key statistical findings include the identification of five critical genes (GPR183, BHLHE41, CD83, SLC25A37, and SELL) associated with macrophage functionality. In vivo validation using immunohistochemistry on clinical samples from 10 breast cancer patients with ovarian metastases confirmed that GPR183, BHLHE41, and CD83 were highly expressed in tumor tissues, while SLC25A37 and SELL were highly expressed in adjacent normal tissues. Furthermore, survival analysis correlated the expression levels of these genes with patient outcomes, thus presenting potential prognostic biomarkers. Our study contributes to a deeper insight of the tumor microenvironment in HR + metastatic breast cancer, and offers potential targets for developing novel therapeutic interventions aimed at mitigating metastatic progression and improving clinical outcomes for HR + breast cancer patients.